2017
DOI: 10.1098/rsif.2017.0185
|View full text |Cite
|
Sign up to set email alerts
|

Mechanotransmission in endothelial cells subjected to oscillatory and multi-directional shear flow

Abstract: Local haemodynamics are linked to the non-uniform distribution of atherosclerosic lesions in arteries. Low and oscillatory (reversing in the axial flow direction) wall shear stress (WSS) induce inflammatory responses in endothelial cells (ECs) mediating disease localization. The objective of this study is to investigate computationally how the flow direction (reflected in WSS variation on the EC surface over time) influences the forces experienced by structural components of ECs that are believed to play impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 67 publications
0
37
0
Order By: Relevance
“…The application of computational/mathematical approaches to address theoretical and experimental questions in biology has significantly broadened our horizons about the EG. Just to name a few, Dabagh et al developed a three‐dimensional, multi‐scale, multi‐component and viscoelastic model of focally adhered endothelial cells, and discussed the contributions of the substructures to mechanotransduction under complicated flow conditions . Eriksson et al performed classical molecular dynamics simulations to study solvation properties of simple cations of biological relevance and reported that the glycocalyx oligosaccharides prefer direct contact with K + over Na + , but that the Na + contacts are longer lived .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of computational/mathematical approaches to address theoretical and experimental questions in biology has significantly broadened our horizons about the EG. Just to name a few, Dabagh et al developed a three‐dimensional, multi‐scale, multi‐component and viscoelastic model of focally adhered endothelial cells, and discussed the contributions of the substructures to mechanotransduction under complicated flow conditions . Eriksson et al performed classical molecular dynamics simulations to study solvation properties of simple cations of biological relevance and reported that the glycocalyx oligosaccharides prefer direct contact with K + over Na + , but that the Na + contacts are longer lived .…”
Section: Introductionmentioning
confidence: 99%
“…Just to name a few, Dabagh et al developed a threedimensional, multi-scale, multi-component and viscoelastic model of focally adhered endothelial cells, and discussed the contributions of the substructures to mechanotransduction under complicated flow conditions. 22 Eriksson et al performed classical molecular dynamics simulations to study solvation properties of simple cations of biological relevance and reported that the glycocalyx oligosaccharides prefer direct contact with K + over Na + , but that the Na + contacts are longer lived. 23 Such computational studies are distinctive as experiments are unlikely to reveal the interactions between endothelium and its ambient environment in such detail.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, in accordance with previous studies are the calculations by Jiang et al of the uncovered transmitted force in the order of 10‐100pN and the presence of a threshold in GAG reduction and changes in mechanotransduction. Together with earlier calculations this could mean that syndecan‐4 transduces force only at a certain threshold of shear stress to which endothelial cells will respond. The presented model also allows to revisit classic topics in understanding the functionality of the endothelial glycocalyx in terms of mechanotransduction, force transmission threshold and its possible relation to the microvascular barrier permeability.…”
mentioning
confidence: 52%
“…Another very important property of the endothelial glycocalyx is the ability to respond to external mechanical forces and to confer shear to the endothelium. Including the important luminal surface of endothelial cells in response to blood flow, recent modelling of the inter‐ and intracellular structures in response to various laminar and disturbed hemodynamic forces revealed that a mechanotransducer within the glycocalyx respond to forces of order 1 to several piconewton …”
mentioning
confidence: 99%
“…The reason is that these models are focused on studying de novo formation of blood vessels, often in the context of cancer. This process is significantly different from reendothelization in an existing vessel, where strong blood flow exists and affects EC migration (Teichmann et al 2012;Shi and Tarbell 2011;Dabagh et al 2017). The novelty of our model lies in coupling the flow model in a 3D channel to a particle-based model of collective migration on the surface of this channel to study the relation between flow patterns and EC migration.…”
Section: Introductionmentioning
confidence: 99%